Immunohistochemical determination of the extracellular matrix modulation in a rat model of choline‐deprived myocardium: the effects of carnitine. (8th December 2015) - Strilakou, Athina; Perelas, Apostolos; Lazaris, Andreas; Papavdi, Asteria; Karkalousos, Petros; Giannopoulou, Ioanna; Kriebardis, Anastasios; Panayiotides, Ioannis; Liapi, Charis
Abstract: Choline has been identified as an essential nutrient with crucial role in many vital biological functions. Recent studies have demonstrated that heart dysfunction can develop in the setting of choline deprivation even in the absence of underlying heart disease. Matrix metalloproteinases (MMPs) are responsible for extracellular matrix degradation, and the dysregulation of MMP‐2 and MMP‐9 has been involved in the pathogenesis of various cardiovascular disorders. The aim of the study was to investigate the role of MMPs and their inhibitors (TIMPs), in the pathogenesis of choline deficiency‐induced cardiomyopathy, and the way they are affected by carnitine supplementation. Male Wistar Albino adult rats were divided into four groups and received standard or choline‐deficient diet with or without L‐carnitine in drinking water (0.15% w/v) for 1 month. Heart tissue immunohistochemistry for MMP‐2, MMP‐9, TIMP‐1, and TIMP‐2 was performed. Choline deficiency was associated with suppressed immunohistochemical expression of MMP‐2 and an increased expression of TIMP‐2 compared to control, while it had no impact on TIMP‐1. MMP‐9 expression was decreased without, however, reaching statistical significance. Carnitine did not affect MMP‐2, MMP‐9, TIMP‐1 or TIMP‐2 expression. The pattern of TIMP and MMP modulation observed in a choline deficiency setting appears to promote fibrosis. Carnitine, although shown to suppress fibrosis, does not seem to affect MMP‐2, MMP‐9, TIMP‐1 or TIMP‐2 expression. Further studies will be required to identify the mechanism underlying the beneficial effects of carnitine.